Neoendogenous In- and Output of Selected Rural Areas: the Case of Economic Cycles in Slovenia - Potočnik Slavič, Irma (Journal for Geography, 2010)
The article focuses on neoendogenous rural development that enables development of endogenous potentials of rural areas (human, social, economic, environmental etc. as development resources of the local territorial level) and external resources (i.e. RD programmes on national and EU level). Four Slovenian case study areas were chosen to test the existence, functioning and outcomes of economic cycles. The survey was undertaken on the smallest spatial-social unit (household), additionally existing voluntary local network (associations) and locally and widely connected economic structures (entrepreneurship) were observed. The research partly confirmed that the activation of endogenous potentials of rural areas is evident through the empowerment of (regional) economic cycles.